Manejo da palha e produção de feno de azevém: ciclagem de nutrientes e rendimento de grãos de arroz irrigado em sucessão - Ferreira, Rafael Bruck (2012)
The deployment of a culture successor as ryegrass (Lolium multiflorum Lam) to irrigated rice in lowland areas could contribute not only to nutrient cycling, but also add to income rice farmer. However, one needs to examine further aspects such as, what better time to make the dessication of ryegrass, so that does not compromise the sowing of the next rice crop. The objective of this study was to evaluate the influence of different managements of ryegrass grown in the off-season irrigated rice on the potential cycling of nitrogen, phosphorus and potassium, the accumulation of these nutrients in the soil profile and its influence on yield grains of rice. For this, an experiment was conducted at the experimental floodplain, using different periods of desiccation and ryegrass hay, and fallow period between crops in the irrigated rice. From the results it can be inferred that the nutrients analyzed potassium has a higher release after the desiccation of ryegrass. Desiccation at 60 days before sowing presents major releases of nitrogen, phosphorus and potassium in ryegrass dry until the time of sowing of rice. Additionally, potassium has a higher accumulation in the soil profile in the run-seeding rice. As composed of herbicide ryegrass were taken closer to the sowing of rice was lower initial establishment of plants, in addition to reducing the nutrient content of rice plants analyzed in the initial stages. The desiccation of rice should be done in advance of 60 days prior to planting rice, to avoid compromising the yield of irrigated rice. The hay production in the floodplain was feasible within two years of study.